2021
DOI: 10.3390/ijerph18189724
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density in Congenital Generalized Lipodystrophy: The Role of Bone Marrow Tissue, Adipokines, and Insulin Resistance

Abstract: Congenital Generalized Lipodystrophy (CGL) is a rare syndrome characterized by the almost total absence of subcutaneous adipose tissue due to the inability of storing lipid in adipocytes. Patients present generalized lack of subcutaneous fat and normal to low weight. They evolve with severe metabolic disorders, non-alcoholic fatty liver disease, early cardiac abnormalities, and infectious complications. Although low body weight is a known risk factor for osteoporosis, it has been reported that type 1 and 2 CGL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Also, later in life, during adolescence, the young patient showed osteolytic lesions which appeared and propagated mainly in the long bones, suggesting that these lesions might be an early sign of lipodystrophy. The presence and progression of bone alterations in CGL has also been described in another interesting study that reviewed 24 cases of genetic CGL; on the basis of all these reports, frequent and peculiar imaging features of skeletal abnormalities, described in generalized lipodystrophic syndromes, are osteosclerosis [20] , lytic lesions, and/or pseudo-osteopoikilosis, often associated with transformation of the bone marrow as also described in a recent review of the literature [19] .…”
Section: Pleiotropic Effects Of Lipodystrophy: Skeletal Alterationsmentioning
confidence: 71%
See 1 more Smart Citation
“…Also, later in life, during adolescence, the young patient showed osteolytic lesions which appeared and propagated mainly in the long bones, suggesting that these lesions might be an early sign of lipodystrophy. The presence and progression of bone alterations in CGL has also been described in another interesting study that reviewed 24 cases of genetic CGL; on the basis of all these reports, frequent and peculiar imaging features of skeletal abnormalities, described in generalized lipodystrophic syndromes, are osteosclerosis [20] , lytic lesions, and/or pseudo-osteopoikilosis, often associated with transformation of the bone marrow as also described in a recent review of the literature [19] .…”
Section: Pleiotropic Effects Of Lipodystrophy: Skeletal Alterationsmentioning
confidence: 71%
“…Since the first description, by Bandeira et al, of altered bone density [18] in subjects affected by Berardinelli-Seip syndrome, more recent reports have shown that children affected by this syndrome grow rapidly and also have advanced bone age [19] . Moreover, several mutations have been described in different genes which might also lead to alterations in several different tissues, including the skeleton.…”
Section: Pleiotropic Effects Of Lipodystrophy: Skeletal Alterationsmentioning
confidence: 99%
“…Low levels of leptin and adiponectin, as well as hyperinsulinemia have already been implicated in the role of increased bone mass in CGL1 and CGL2 ( 14 , 32 ). However, insulin resistance is also present in CGL3 and CGL4 without elevated BMD, and studies with adipokines are still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the study by Jiang et al provided substantial evidence of a consistent relationship between low levels of HDL-C and an increase in BMD in the context of MetS while also indicating that elevated triglyceride levels positively correlate with BMD 50 . Reports have suggested that individuals with insulin resistance and elevated insulin levels due to MetS might experience an increase in BMD 51 . Animal experiments further corroborated these findings, demonstrating that insulin could enhance BMD by facilitating osteocalcin signaling, aligning with our study's conclusions 52 .…”
Section: Discussionmentioning
confidence: 99%